2021
DOI: 10.3390/plants10091887
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression, Tissue-Specific Distribution, and Posttranslational Controls of Phosphoenolpyruvate Carboxylase

Abstract: Phosphoenolpyruvate carboxylase (PEPC) is a ubiquitous cytosolic enzyme, which is crucial for plant carbon metabolism. PEPC participates in photosynthesis by catalyzing the initial fixation of atmospheric CO2 and is abundant in both C4 and crassulacean acid metabolism leaves. PEPC is differentially expressed at different stages of plant development, mostly in leaves, but also in developing seeds. PEPC is known to show tissue-specific distribution in leaves and in other plant organs, such as roots, stems, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Since we have shown that PEPc contribution to Malate production was reduced in dark compared to light conditions, this result can only be explained by a higher transport of OAA/Malate from the cytosol to the mitochondria in dark conditions ( Figure 8 ). This idea is supported by the fact that PEPc is majorly localized to the cytosol (Caburatan and Park, 2021) and the recent identification of a mitochondrial malate importer in Arabidopsis with a decisive impact on mitochondrial respiration (Lee et al, 2021). Whether a higher malate import into mitochondria allows to increase the absolute metabolic flux of the TCA cycle in dark conditions in our experimental set-up remains to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Since we have shown that PEPc contribution to Malate production was reduced in dark compared to light conditions, this result can only be explained by a higher transport of OAA/Malate from the cytosol to the mitochondria in dark conditions ( Figure 8 ). This idea is supported by the fact that PEPc is majorly localized to the cytosol (Caburatan and Park, 2021) and the recent identification of a mitochondrial malate importer in Arabidopsis with a decisive impact on mitochondrial respiration (Lee et al, 2021). Whether a higher malate import into mitochondria allows to increase the absolute metabolic flux of the TCA cycle in dark conditions in our experimental set-up remains to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…Such shift could be attributed to both increased PEPc activity and TCA cycle inhibition in the light compared to dark conditions. Interestingly, PEPc activity is positively regulated by its light-dependent thioredoxin-mediated phosphorylation in C 3 and C 4 plants (Caburatan and Park, 2021). In the light, the lower respiration rate measured compared to dark conditions has been partly attributed to an inhibition of PDH and TCA cycle-derived decarboxylations (Tcherkez et al, 2005;Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEPc activity is positively regulated by its light-dependent thioredoxin-mediated phosphorylation in C 3 and C 4 plants ( Caburatan and Park, 2021 ). Consequently, PEPc is expected to be more active in the light than in the dark, as recently suggested in guard cell cultures based on the differential 13 C enrichment found for the C1 of glutamate ( Lima et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most non-photosynthetic PEPCs are cytosolic isoforms, but a chloroplast-targeted isoform was found in grass species rice ( Masumoto et al, 2010 ). Cytosolic PEPCs are predominant in plant species with multiple isoforms, from which gene expression patterns differ ( Caburatan and Park, 2021 ). In rice, four cytosolic PEPCs, one chloroplast PEPC, and one bacterial-type PEPC are known, but biological roles of these PEPCs seem to be not identical ( Masumoto et al, 2010 ; Yamamoto et al, 2014a , 2015 ).…”
Section: Introductionmentioning
confidence: 99%